2016
DOI: 10.1111/1365-2435.12792
|View full text |Cite
|
Sign up to set email alerts
|

Plant genotypic variation and intraspecific diversity trump soil nutrient availability to shape old‐field structure and function

Abstract: Summary Individual plant genotypes as well as genotypic diversity can shape the structure and function of ecosystems; however, the abiotic environment may modify these genotypic influences on ecosystem‐level responses. To explore how the interactions between plant genotype, genotypic diversity and soil nutrient availability affect the structure and function of a temperate grassland ecosystem, we manipulated the genotypic diversity of a common perennial herbaceous plant, Solidago altissima (single genotype mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Research supports the use of genetically diverse plant material for restoration efforts because genetically diverse populations are generally more resilient to disease, stress, and climatic extremes (Burdon ; Reusch et al ; Guarino et al ), more likely to persist and spread (Hughes & Stachowicz ; Crawford & Whitney ), and support more ecosystem services (Crutsinger et al ; Souza et al ). Yet in practice many reintroduced plant populations have lower genetic diversity than remnant populations (Fant et al ; Neale ).…”
Section: Introductionmentioning
confidence: 99%
“…Research supports the use of genetically diverse plant material for restoration efforts because genetically diverse populations are generally more resilient to disease, stress, and climatic extremes (Burdon ; Reusch et al ; Guarino et al ), more likely to persist and spread (Hughes & Stachowicz ; Crawford & Whitney ), and support more ecosystem services (Crutsinger et al ; Souza et al ). Yet in practice many reintroduced plant populations have lower genetic diversity than remnant populations (Fant et al ; Neale ).…”
Section: Introductionmentioning
confidence: 99%
“…and key ecosystem functions like productivity (Abbott, Grosberg, Williams, & Stachowicz, 2017) and nutrient cycling (Souza, Stuble, Genung, & Classen, 2017) are increasingly well documented.…”
Section: Positive Relationships Between Intraspecific Genetic Diversitymentioning
confidence: 99%
“…Positive relationships between intraspecific genetic diversity and key ecosystem functions like productivity (Abbott, Grosberg, Williams, & Stachowicz, 2017) and nutrient cycling (Souza, Stuble, Genung, & Classen, 2017) are increasingly well documented. Intraspecific genetic diversity can impact ecosystem functioning via niche partitioning driven by complementarity among genotypes (Raffard, Santoul, Cucherousset, & Blanchet, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Over years, most studies have confirmed that species richness has significant positive direct effects on a single ecosystem function such as biomass production (van der Plas, 2019). Meanwhile, there is increasing evidence that genotype richness plays an important role in affecting a single ecosystem function (Schweitzer et al, 2011;Souza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%